Enhancing EFL students’ reading learning process in COVID-19 pandemic through Nearpod - Pupah, Emmas Mas; Sholihah, Umi (Englisia Journal, 2022)
This research aims to enhance students’ reading learning process using a genre-based approach during the COVID-19 pandemic through Nearpod. Action research with four stages was applied as a research design. The qualitative data were collected through interviews and teacher’s field notes, while the quantitative data were obtained by students’ reading pre-test and post-test. The qualitative data were analyzed by assembling the data, coding the data, building interpretations, and reporting the outcomes. Meanwhile, the quantitative data were analyzed using descriptive quantitative analysis. Findings demonstrated that students learned how to determine the main idea, make an inference, and distinguish detailed information from the texts. They also considered Nearpod as an accommodating and encouraging tool in learning. The teacher addressed how to reinforce the students’ reading learning process by deep consideration, preparation, and reflection to ensure that Nearpod worked properly. The statistical report of students’ scores for the pre-test and post-test showed improvement from 64.7 to 84.8. The average students’ post-test score was greater than the pre-test. This study revealed that the Nearpod program successfully supported the reading learning process for students because of its user-friendliness and it enabled teachers to monitor students’ progress during the teaching process.